A sand-walled architectural coating and preparation method thereof

By using the combination of components such as polyurethane emulsion, ZnO-MgO catalyst, TCA hybrid, diallylamine, calcined kaolin and crop charcoal in the air purification coating, the problem of incomplete removal of formaldehyde in the existing air purification coating is solved, and the problem of complete removal of formaldehyde is achieved. More efficient formaldehyde removal and optimization of coating performance.

CN119119851BActive Publication Date: 2025-02-11GUANGDONG LIDA NEW MATERIAL TECH CO LTD

Patent Information

Application Number
CN202411596721.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-02-11
Estimated Expiration
2044-11-11

AI Technical Summary

Technical Problem

The existing air purification coatings are incomplete in removing formaldehyde, and the absorption of activated carbon is limited, which may lead to secondary contamination of formaldehyde during adsorption saturation.

Method used

A sand-walled building coating is used, which consists of polyurethane emulsion, ZnO-MgO catalyst, TCA hybrid, diallylamine, calcined kaolin, crop charcoal and coating additives. Through the combination of these components, effective removal of formaldehyde is achieved. .

Benefits of technology

Through the use of ZnO-MgO catalyst with a porous structure, the oxidation and decomposition efficiency of formaldehyde can be significantly improved. TCA hybrids build a dense cross-linking network, enhance the water resistance and stain resistance of the coating, and provide good adsorption and purification effects of crop charcoals. Comprehensively realizes the improvement of formaldehyde removal performance and the optimization of multiple performances of coatings.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The present invention belongs to the technical field of coatings, and specifically relates to a sand-walled architectural coating and a preparation method thereof. The sand-walled architectural coating is composed of the following components by mass: 35-50 parts of polyurethane emulsion, 5-8 parts of ZnO-MgO catalyst, 8-12 parts of TCA hybrid, 5-8 parts of diallylamine, 10-15 parts of calcined kaolin, 5-10 parts of crop carbonization, 3-5 parts of coating additives, and 15-20 parts of water; wherein the TCA hybrid is mainly prepared by reacting cardanol glycidyl ether, aminopropyl triethoxysilane and tannic acid. The preparation method of the sand-walled architectural coating of the present invention is simple, and the prepared sand-walled architectural coating has excellent formaldehyde removal performance and good water resistance and stain resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of coatings, and in particular relates to a sand-walled architectural coating and a preparation method thereof. Background Art

[0002] In recent years, the issue of formaldehyde released from building decoration materials has attracted more and more attention. Formaldehyde mainly comes from materials such as plywood and joinery boards. It is a colorless, soluble, irritating gas that is quite harmful to the human body. At present, some formaldehyde-removing air purification products have been gradually developed at home and abroad, including air purification coatings, activated carbon, air purifiers, etc. Among them, air purification coatings, as a new type of formaldehyde-removing technical material, have broad market prospects.

[0003] The Chinese patent application document with publication number CN108329778A discloses a production process of diatom mud and activated carbon composite interior decoration paint. The paint is composed of the following raw materials in parts by weight: dispersant, surfactant, defoamer, ethylene glycol, titanium dioxide, diatomaceous earth, pure acrylic emulsion, polyurethane thickener, preservative, mildewproof agent, film-forming aid, water, and activated carbon; the activated carbon in the paint can be in contact with the surrounding air to a large extent due to its own developed pore structure and surface area, and passively adsorb some pollutants into its own pores, effectively playing the role of sterilization, deodorization, and air purification.

[0004] However, activated carbon has limited absorption capacity for formaldehyde and cannot completely absorb it. It can absorb and purify formaldehyde in the initial stage of purification. When its adsorption is saturated, a dynamic balance of adsorption-desorption will exist between formaldehyde in the air and the paint. Therefore, under certain conditions, the adsorbed formaldehyde may be released back into the indoor environment, causing secondary pollution.

[0005] Sand-walled architectural paint is mainly a sand-like architectural paint made of synthetic resin emulsion and colored sand particles as raw materials. The unique texture and low cost of sand-walled paint make it an ideal choice for interior and exterior wall decoration. In view of this, the present invention provides a sand-walled architectural paint that can remove formaldehyde relatively thoroughly and a preparation method thereof, thereby reducing the probability of formaldehyde diffusing into the air. Summary of the invention

[0006] The existing coatings have the problem of incomplete removal of formaldehyde. In order to solve this problem, the present invention provides a sand-walled architectural coating and a preparation method thereof.

[0007] In order to achieve the purpose of the present invention, the present invention adopts the following technical solutions:

[0008] In a first aspect, the present invention provides a sand-walled architectural coating, wherein the sand-walled architectural coating is composed of the following components in parts by weight:

[0009] 35-50 parts of polyurethane emulsion, 5-8 parts of ZnO-MgO catalyst, 8-12 parts of TCA hybrid, 5-8 parts of diallylamine, 10-15 parts of calcined kaolin, 5-10 parts of carbonized crops, 3-5 parts of coating additives, and 15-20 parts of water;

[0010] The TCA hybrid is mainly prepared by reacting cardanol glycidyl ether, aminopropyl triethoxysilane and tannic acid.

[0011] Calcined kaolin has low reactivity to light and adding it to paint can make the paint have good weather resistance.

[0012] Diallylamine can react with formaldehyde. The carbonyl carbon in the formaldehyde molecule is partially positively charged, and the nitrogen atom in the diallylamine molecule has a lone pair of electrons, which has strong nucleophilicity. The nitrogen atom of diallylamine attacks the carbonyl carbon of formaldehyde through nucleophilic attack to form imine compounds, which can assist in the removal of formaldehyde.

[0013] Preferably, the preparation method of the ZnO-MgO catalyst comprises the following steps:

[0014] Zinc nitrate, magnesium chloride, glucose and water are uniformly mixed, heated and calcined, and cooled to obtain a ZnO-MgO catalyst.

[0015] Zinc nitrate and magnesium chloride decompose at high temperature to form zinc oxide and magnesium oxide respectively. Glucose burns during calcination to produce gases such as carbon dioxide and water vapor. These gases form pores in magnesium oxide and zinc oxide crystals during the escape process, thus forming a porous structure. The presence of MgO can improve the charge separation efficiency of ZnO and reduce the recombination probability of electron-hole pairs. The prepared ZnO-MgO catalyst can purify indoor and outdoor air and degrade harmful gases such as formaldehyde and benzene in the air. The porous structure gives the ZnO-MgO catalyst a larger specific surface area, which enables it to provide more active sites, increase the contact area with the reactants, and improve the reaction efficiency.

[0016] Preferably, the mass ratio of zinc nitrate, magnesium chloride and glucose is 1:(1-2):(3-4); by optimizing and adjusting the ratio of zinc nitrate, magnesium chloride and glucose, a ZnO-MgO catalyst with uniform pore distribution is formed.

[0017] Preferably, the calcination temperature is 750-800° C., and the calcination time is 3-5 h.

[0018] Preferably, the heating rate of the calcination is 3-5°C / min.

[0019] Preferably, the method for preparing the TCA hybrid comprises the following steps:

[0020] (1) Under an inert atmosphere, cardanol glycidyl ether and aminopropyl triethoxysilane are uniformly mixed and heated to react to obtain a mixture A;

[0021] (2) Mixture A and anhydrous ethanol are mixed evenly to obtain solution A, tannic acid and Tris-HCl buffer are mixed evenly to obtain solution B, solution A and solution B are mixed evenly to react, and anhydrous ethanol is removed by rotary evaporation to obtain TCA hybrid.

[0022] Preferably, in step (1), the mass ratio of cardanol glycidyl ether to aminopropyltriethoxysilane is (2-4):1; the reaction temperature is 80-90°C, and the reaction time is 1-2h.

[0023] Preferably, in step (2), the amount of tannic acid used is 50%-80% of the mass of aminopropyltriethoxysilane.

[0024] Preferably, the pH of the Tris-HCl buffer is 8-8.5.

[0025] Preferably, the method for preparing the carbonized crop comprises the following steps:

[0026] The corn straw, wheat straw and rice husk are crushed and mixed evenly to obtain crop particles, and the crop particles are carbonized to obtain crop carbonized materials.

[0027] The carbonized crops have a certain surface roughness, which can increase adhesion, which helps to improve the durability and stability of the coating and reduce the risk of coating peeling and cracking; compared with traditional colored sand, crop carbonization is usually lighter, which can reduce the overall weight of the coating and reduce the production cost of the coating.

[0028] Preferably, the temperature of the carbonization treatment is 450-550° C., and the time of the carbonization treatment is 1-3 hours. Within this temperature and time range, the carbonized crop obtained has a stable structure.

[0029] Preferably, the particle size of the carbonized crop is 60-100 meshes; the carbonized crop is of moderate size, and is easily dispersed and evenly distributed in the coating.

[0030] Preferably, the coating additive is selected from one or more of a bactericidal preservative and a thickener.

[0031] In a second aspect, the present invention provides a method for preparing the above-mentioned sand-walled architectural coating, comprising the following steps:

[0032] The polyurethane emulsion, ZnO-MgO catalyst, TCA hybrid, diallylamine and water are mixed evenly, calcined kaolin and carbonized crops are added and mixed evenly, and then the coating additives are added and mixed evenly to obtain a sand-walled architectural coating.

[0033] In summary, the beneficial effects of the present invention are as follows:

[0034] (1) The present invention utilizes glucose to decompose at high temperature to form a carbon skeleton to form a porous ZnO / MgO catalyst. When the surface of the ZnO / MgO catalyst is stimulated by ultraviolet rays, electron transitions can be stimulated to form highly active electron-hole pairs and migrate to the surface to generate active oxides such as hydroxyl free radicals and hydrogen peroxide. The strong oxidizing properties of these active oxides can oxidatively decompose formaldehyde into harmless substances such as carbon dioxide and water, thereby achieving the purpose of removing formaldehyde. The porous structure formed by glucose increases the specific surface area of ​​the ZnO-MgO catalyst, so that it can accommodate more formaldehyde molecules, increase the probability of collision between formaldehyde and active sites, and promote the oxidative decomposition reaction of formaldehyde.

[0035] (2) The TCA hybrid prepared by the present invention realizes high-efficiency stain resistance and water resistance by constructing a dense cross-linked network; the cardanol glycidyl ether reacts with aminopropyl triethoxysilane to form a cross-linked network structure, and tannic acid is introduced at the same time. On the one hand, the phenolic hydroxyl groups in the tannic acid can react with the amino groups of aminopropyl triethoxysilane to form a denser cross-linked network, thereby increasing the cross-linking density of the coating and enhancing the physical properties of the coating; on the other hand, the chemical stability of the polyphenol structure of tannic acid and the long chain structure of cardanol glycidyl ether can resist the erosion of chemical stains and reduce the pollution caused by chemical reactions. The siloxane group of aminopropyl triethoxysilane has a certain hydrophobicity, which can reduce the attachment of water-based stains; at the same time, the ZnO-MgO catalyst can decompose some of the pollutants adsorbed on the surface of the coating, giving the coating a self-cleaning property;

[0036] (3) The present invention uses carbonized waste crops as aggregate to bring a rough texture and performance to the coating. At the same time, the porous structure and large specific surface area of ​​the carbonized crops can absorb part of the formaldehyde and purify the air. The addition of carbonized crops can also enhance the wear resistance and covering ability of the coating.

[0037] (4) The ZnO-MgO catalyst and the carbonized crop products added to the coating formula of the present invention can achieve the purpose of adsorbing and removing formaldehyde, the TCA hybrid can improve the water resistance and stain resistance of the coating, and the environmentally friendly polyurethane emulsion and coating additives are used in the coating formula, and no other harmful by-products are generated; the preparation method of the sand-walled architectural coating of the present invention is simple, and the prepared sand-walled architectural coating has excellent formaldehyde removal performance and good water resistance and stain resistance. DETAILED DESCRIPTION

[0038] The technical solutions in the embodiments of the present invention are described clearly and completely below.

[0039] In the following examples, the thickener is hydroxyethyl cellulose; the bactericidal preservative is Proxel BD20.

[0040] Example 1

[0041] A sand-walled architectural coating, comprising the following components in parts by weight:

[0042] 35 parts of polyurethane emulsion, 6 parts of ZnO-MgO catalyst, 10 parts of TCA hybrid, 8 parts of diallylamine, 13 parts of calcined kaolin, 10 parts of carbonized crops, 2 parts of bactericide and preservative, 2 parts of thickener, and 15 parts of water;

[0043] Wherein, the ZnO-MgO catalyst is prepared by the method of "preparing ZnO-MgO catalyst" as described below;

[0044] TCA hybrids were prepared by the method described below in “Preparation of TCA hybrids”;

[0045] The carbonized crop material is prepared by the method of "preparing carbonized crop material" described below.

[0046] The specific steps of a method for preparing a sand-walled architectural coating are as follows:

[0047] (1) Preparation of ZnO-MgO catalyst

[0048] Add 10 g zinc nitrate, 10 g magnesium chloride, 30 g glucose and 80 mL water into a three-necked flask, stir evenly, transfer the mixed solution to a muffle furnace, heat to 750 ° C at a rate of 5 ° C / min, calcine for 5 h, and cool naturally to room temperature to obtain a ZnO-MgO catalyst;

[0049] (2) Preparation of TCA hybrids

[0050] Under a nitrogen atmosphere, 40 g of cardanol glycidyl ether and 15 g of aminopropyl triethoxysilane were added to the reaction kettle, stirred evenly, and heated to 90° C. for reaction for 2 h to obtain a mixture A;

[0051] Add 30 g of mixture A and 80 mL of anhydrous ethanol to a beaker, stir evenly to obtain solution A, add 7.5 g of tannic acid and 50 mL of Tris-HCl buffer with a pH of 8.5 to a beaker, stir evenly to obtain solution B; add solution A to solution B, stir at room temperature for 12 h, and remove anhydrous ethanol by rotary evaporation at 60° C. and -0.1 MPa to obtain TCA hybrid;

[0052] (3) Preparation of carbonized crops

[0053] 50g corn straw, 50g wheat straw and 30g rice husk were crushed and mixed evenly to obtain crop particles, the crop particles were put into a carbonization furnace for carbonization treatment at 450°C for 2h to obtain crop carbonized products, which were crushed and passed through a 60-mesh sieve for later use;

[0054] (4) Preparation of sand-walled architectural coatings

[0055] Add polyurethane emulsion, ZnO-MgO catalyst, TCA hybrid, diallylamine and water into a disperser, stir at 500 r / min for 1 h, add calcined kaolin and stir at 1500 r / min for 30 min, add carbonized crop and stir at 700 r / min for 20 min, add a bactericide and preservative, and finally add a thickener and stir for 10 min to obtain a sand-walled architectural coating.

[0056] Example 2

[0057] A sand-walled architectural coating, comprising the following components in parts by weight:

[0058] 40 parts of polyurethane emulsion, 5 parts of ZnO-MgO catalyst, 8 parts of TCA hybrid, 5 parts of diallylamine, 15 parts of calcined kaolin, 8 parts of carbonized crops, 1 part of bactericidal preservative, 2 parts of thickener, and 20 parts of water;

[0059] Wherein, the ZnO-MgO catalyst is prepared by the method of "preparing ZnO-MgO catalyst" as described below;

[0060] TCA hybrids were prepared by the method described below in “Preparation of TCA hybrids”;

[0061] The carbonized crop material is prepared by the method of "preparing carbonized crop material" described below.

[0062] The specific steps of a method for preparing a sand-walled architectural coating are as follows:

[0063] (1) Preparation of ZnO-MgO catalyst

[0064] Add 10 g zinc nitrate, 15 g magnesium chloride, 40 g glucose and 100 mL water into a three-necked flask and stir evenly. Transfer the mixed solution to a muffle furnace and heat it to 800 °C at a rate of 5 °C / min for calcination for 4 h. Cool it naturally to room temperature to obtain a ZnO-MgO catalyst.

[0065] (2) Preparation of TCA hybrids

[0066] Under a nitrogen atmosphere, 50 g of cardanol glycidyl ether and 15 g of aminopropyl triethoxysilane were added to the reaction kettle, stirred evenly, and heated to 85° C. for reaction for 1 h to obtain a mixture A;

[0067] Add 30 g of mixture A and 80 mL of anhydrous ethanol to a beaker, stir evenly to obtain solution A, add 9 g of tannic acid and 50 mL of Tris-HCl buffer with a pH of 8 to a beaker, stir evenly to obtain solution B; add solution A to solution B, stir at room temperature for 12 h, and remove anhydrous ethanol by rotary evaporation at 60° C. and -0.1 MPa to obtain TCA hybrid;

[0068] (3) Preparation of carbonized crops

[0069] 40g corn straw, 40g wheat straw and 40g rice husk were crushed and mixed evenly to obtain crop particles, the crop particles were put into a carbonization furnace for carbonization treatment at 550°C for 1 hour to obtain crop carbonized products, which were crushed and passed through an 80-mesh sieve for later use;

[0070] (4) Preparation of sand-walled architectural coatings

[0071] Add polyurethane emulsion, ZnO-MgO catalyst, TCA hybrid, diallylamine and water into a disperser, stir at a speed of 600 r / min for 30 minutes, add calcined kaolin and stir at a speed of 1600 r / min for 30 minutes, add carbonized crops and stir at a speed of 800 r / min for 20 minutes, then add a bactericide and preservative, and finally add a thickener and stir for 10 minutes to obtain a sand-walled architectural coating.

[0072] Example 3

[0073] A sand-walled architectural coating, comprising the following components in parts by weight:

[0074] 50 parts of polyurethane emulsion, 8 parts of ZnO-MgO catalyst, 8 parts of TCA hybrid, 5 parts of diallylamine, 10 parts of calcined kaolin, 5 parts of carbonized crop, 2 parts of bactericidal preservative, 3 parts of thickener, and 15 parts of water;

[0075] Wherein, the ZnO-MgO catalyst is prepared by the method of "preparing ZnO-MgO catalyst" as described below;

[0076] TCA hybrids were prepared by the method described below in “Preparation of TCA hybrids”;

[0077] The carbonized crop material is prepared by the method of "preparing carbonized crop material" described below.

[0078] The specific steps of a method for preparing a sand-walled architectural coating are as follows:

[0079] (1) Preparation of ZnO-MgO catalyst

[0080] Add 10 g zinc nitrate, 10 g magnesium chloride, 35 g glucose and 80 mL water into a three-necked flask, stir evenly, transfer the mixed solution to a muffle furnace, heat to 770 ° C at a rate of 3 ° C / min, calcine for 5 h, and cool naturally to room temperature to obtain a ZnO-MgO catalyst;

[0081] (2) Preparation of TCA hybrids

[0082] Under a nitrogen atmosphere, 30 g of cardanol glycidyl ether and 15 g of aminopropyl triethoxysilane were added to the reaction kettle, stirred evenly, and heated to 85° C. for reaction for 1.5 h to obtain a mixture A;

[0083] Add 30 g of mixture A and 80 mL of anhydrous ethanol to a beaker, stir evenly to obtain solution A, add 10.5 g of tannic acid and 50 mL of Tris-HCl buffer with a pH of 8.5 to a beaker, stir evenly to obtain solution B; add solution A to solution B, stir at room temperature for 12 h, and remove anhydrous ethanol by rotary evaporation at 60° C. and -0.1 MPa to obtain TCA hybrid;

[0084] (3) Preparation of carbonized crops

[0085] 40g corn straw, 40g wheat straw and 40g rice husk were crushed and mixed evenly to obtain crop particles, and the crop particles were put into a carbonization furnace for carbonization treatment at 500°C for 3h to obtain crop carbonized products, which were crushed and passed through an 80-mesh sieve for later use;

[0086] (4) Preparation of sand-walled architectural coatings

[0087] Add polyurethane emulsion, ZnO-MgO catalyst, TCA hybrid, diallylamine and water into a disperser, stir at 500 r / min for 1 h, add calcined kaolin and stir at 1700 r / min for 30 min, add carbonized crop and stir at 800 r / min for 20 min, add a bactericide and preservative, and finally add a thickener and stir for 10 min to obtain a sand-walled architectural coating.

[0088] Example 4

[0089] A sand-walled architectural coating, comprising the following components in parts by weight:

[0090] 45 parts of polyurethane emulsion, 8 parts of ZnO-MgO catalyst, 12 parts of TCA hybrid, 8 parts of diallylamine, 13 parts of calcined kaolin, 8 parts of carbonized crops, 3 parts of thickener, and 15 parts of water;

[0091] Wherein, the ZnO-MgO catalyst is prepared by the method of "preparing ZnO-MgO catalyst" as described below;

[0092] TCA hybrids were prepared by the method described below in “Preparation of TCA hybrids”;

[0093] The carbonized crop material is prepared by the method of "preparing carbonized crop material" described below.

[0094] The specific steps of a method for preparing a sand-walled architectural coating are as follows:

[0095] (1) Preparation of ZnO-MgO catalyst

[0096] Add 10 g zinc nitrate, 20 g magnesium chloride, 40 g glucose and 100 mL water into a three-necked flask and stir evenly. Transfer the mixed solution to a muffle furnace and heat it to 800 °C at a rate of 5 °C / min for calcination for 3 h. Cool it naturally to room temperature to obtain a ZnO-MgO catalyst.

[0097] (2) Preparation of TCA hybrids

[0098] Under a nitrogen atmosphere, 60 g of cardanol glycidyl ether and 15 g of aminopropyl triethoxysilane were added to the reaction kettle, stirred evenly, and heated to 80° C. for reaction for 1 h to obtain a mixture A;

[0099] Add 30 g of mixture A and 80 mL of anhydrous ethanol to a beaker, stir evenly to obtain solution A, add 12 g of tannic acid and 50 mL of Tris-HCl buffer with a pH of 8 to a beaker, stir evenly to obtain solution B; add solution A to solution B, stir at room temperature for 12 h, and remove anhydrous ethanol by rotary evaporation at 60° C. and -0.1 MPa to obtain TCA hybrid;

[0100] (3) Preparation of carbonized crops

[0101] 50g corn straw, 50g wheat straw and 40g rice husk were crushed and mixed evenly to obtain crop particles, and the crop particles were put into a carbonization furnace for carbonization treatment at 500°C for 2h to obtain crop carbonized products, which were crushed and passed through a 100-mesh sieve for later use;

[0102] (4) Preparation of sand-walled architectural coatings

[0103] Add polyurethane emulsion, ZnO-MgO catalyst, TCA hybrid, diallylamine and water into a disperser, stir at 600 r / min for 1 h, add calcined kaolin and stir at 1500 r / min for 30 min, add carbonized crop and stir at 700 r / min for 20 min, then add thickener and stir for 10 min to obtain a sand-walled architectural coating.

[0104] Example 5

[0105] A sand-walled architectural coating, comprising the following components in parts by weight:

[0106] 40 parts of polyurethane emulsion, 5 parts of ZnO-MgO catalyst, 10 parts of TCA hybrid, 8 parts of diallylamine, 10 parts of calcined kaolin, 10 parts of carbonized crops, 2 parts of bactericide and preservative, 2 parts of thickener, and 20 parts of water;

[0107] Wherein, the ZnO-MgO catalyst is prepared by the method of "preparing ZnO-MgO catalyst" as described below;

[0108] TCA hybrids were prepared by the method described below in “Preparation of TCA hybrids”;

[0109] The carbonized crop material is prepared by the method of "preparing carbonized crop material" described below.

[0110] The specific steps of a method for preparing a sand-walled architectural coating are as follows:

[0111] (1) Preparation of ZnO-MgO catalyst

[0112] Add 10 g zinc nitrate, 15 g magnesium chloride, 40 g glucose and 100 mL water into a three-necked flask, stir evenly, transfer the mixed solution to a muffle furnace, heat to 750 °C at a rate of 3 °C / min, calcine for 4 h, and cool naturally to room temperature to obtain a ZnO-MgO catalyst;

[0113] (2) Preparation of TCA hybrids

[0114] Under a nitrogen atmosphere, 50 g of cardanol glycidyl ether and 15 g of aminopropyl triethoxysilane were added to the reaction kettle, stirred evenly, and heated to 90° C. for reaction for 2 h to obtain a mixture A;

[0115] Add 30 g of mixture A and 80 mL of anhydrous ethanol to a beaker, stir evenly to obtain solution A, add 10.5 g of tannic acid and 50 mL of Tris-HCl buffer with a pH of 8.5 to a beaker, stir evenly to obtain solution B; add solution A to solution B, stir at room temperature for 12 h, and remove anhydrous ethanol by rotary evaporation at 60° C. and -0.1 MPa to obtain TCA hybrid;

[0116] (3) Preparation of carbonized crops

[0117] 50g corn straw, 50g wheat straw and 30g rice husk were crushed and mixed evenly to obtain crop particles, the crop particles were put into a carbonization furnace for carbonization treatment at 450°C for 2h to obtain crop carbonized products, which were crushed and passed through a 60-mesh sieve for later use;

[0118] (4) Preparation of sand-walled architectural coatings

[0119] Add polyurethane emulsion, ZnO-MgO catalyst, TCA hybrid, diallylamine and water into a disperser, stir at 600 r / min for 1 h, add calcined kaolin and stir at 1500 r / min for 30 min, add carbonized crop and stir at 800 r / min for 20 min, add a bactericide and preservative, and finally add a thickener and stir for 10 min to obtain a sand-walled architectural coating.

[0120] Comparative Example 1

[0121] The difference from Example 1 is that no ZnO-MgO catalyst is added in this comparative example, and the rest is the same as Example 1.

[0122] Comparative Example 2

[0123] The difference from Example 1 is that no TCA hybrid is added in this comparative example, and the rest is the same as Example 1.

[0124] Comparative Example 3

[0125] The difference from Example 1 is that diallylamine is not added in this comparative example, and the rest is the same as Example 1.

[0126] Comparative Example 4

[0127] The difference from Example 1 is that the mass ratio of zinc nitrate, magnesium chloride and glucose in this comparative example is 1:1:0.5.

[0128] Related tests

[0129] According to JC / T 1074-2021 "Purification Performance of Indoor Air Purification Functional Coating Materials", the formaldehyde purification efficiency and the durability of the formaldehyde purification effect of the sand-walled architectural coatings prepared in Examples 1 to 5 and Comparative Examples 1 to 4 were tested, and the test results are shown in Table 1.

[0130] Table 1 Test results

[0131]

[0132] As can be seen from Table 1, the sand-walled architectural coatings prepared in Examples 1 to 5 have excellent formaldehyde removal performance.

[0133] According to JG / T 24-2018 "Synthetic Resin Emulsion Sand-Walled Architectural Coatings", the sand-walled architectural coatings prepared in Examples 1 to 5 and Comparative Examples 1 to 4 were tested respectively, and the test results are shown in Table 2.

[0134] Table 2 Test results

[0135]

[0136] As can be seen from Table 2, the sand-walled architectural coatings prepared in Examples 1 to 5 have good water resistance, stain resistance, weather resistance and other properties.

[0137] The above is an exemplary description of the present invention. It should be noted that, without departing from the core of the present invention, any simple deformation, modification or equivalent replacement that can be done by other technicians in this field without expending creative labor falls within the protection scope of the present invention.

Claims

1. A sand-walled architectural coating, characterized in that: The sand-walled architectural coating is composed of the following components in parts by weight: 35-50 parts of polyurethane emulsion, 5-8 parts of ZnO-MgO catalyst, 8-12 parts of TCA hybrid, 5-8 parts of diallylamine, 10-15 parts of calcined kaolin, 5-10 parts of carbonized crops, 3-5 parts of coating additives, and 15-20 parts of water; The preparation method of the ZnO-MgO catalyst comprises the following steps: Mix zinc nitrate, magnesium chloride, glucose and water uniformly, heat and calcine, and cool to obtain a ZnO-MgO catalyst; The preparation method of the TCA hybrid comprises the following steps: (1) Under an inert atmosphere, cardanol glycidyl ether and aminopropyl triethoxysilane are uniformly mixed and heated to react to obtain a mixture A; (2) Mixture A and anhydrous ethanol are mixed evenly to obtain solution A, tannic acid and Tris-HCl buffer are mixed evenly to obtain solution B, solution A and solution B are mixed evenly to react, and anhydrous ethanol is removed by rotary evaporation to obtain TCA hybrid.

2. The sand-walled architectural coating according to claim 1, characterized in that: The mass ratio of the zinc nitrate, magnesium chloride and glucose is 1:(1-2):(3-4).

3. The sand-walled architectural coating according to claim 1, characterized in that: The calcination temperature is 750-800° C., and the calcination time is 3-5 hours.

4. The sand-walled architectural coating according to claim 1, characterized in that: In the step (1), the mass ratio of cardanol glycidyl ether to aminopropyl triethoxysilane is (2-4):1; the reaction temperature is 80-90°C, and the reaction time is 1-2h.

5. The sand-walled architectural coating according to claim 1, characterized in that: In step (2), the amount of tannic acid used is 50%-80% of the mass of aminopropyltriethoxysilane.

6. The sand-walled architectural coating according to claim 1, characterized in that: The method for preparing the carbonized crop comprises the following steps: The corn straw, wheat straw and rice husk are crushed and mixed evenly to obtain crop particles, and the crop particles are carbonized to obtain crop carbonized materials.

7. The sand-walled architectural coating according to claim 1, characterized in that: The coating additive is selected from one or more of a bactericidal preservative and a thickener.

8. A method for preparing a sand-walled architectural coating according to any one of claims 1 to 7, characterized in that: The steps include: The polyurethane emulsion, ZnO-MgO catalyst, TCA hybrid, diallylamine and water are mixed evenly, calcined kaolin and carbonized crops are added and mixed evenly, and then the coating additives are added and mixed evenly to obtain a sand-walled architectural coating.

Citation Information

Patent Citations

  • Production process of diatom ooze and activated carbon composite indoor decorative coating

    CN108329778A

  • Water-based acrylic acid resin for chemically adsorbing and degrading formaldehyde and preparation method of water-based acrylic acid resin

    CN110156930A

  • Preparation method of molybdenum carbide hydrogenolysis lignin catalyst

    CN113856718A

Cited By

  • Architectural coating filler integrating air purification, antibiosis and corrosion prevention functions and preparation and application thereof

    CN121086575A